2021
DOI: 10.1108/bij-07-2020-0371
|View full text |Cite
|
Sign up to set email alerts
|

The internet of things in the food supply chain: adoption challenges

Abstract: PurposeThe food supply chain (FSC) challenges coupled with global disruptions, such as the recent coronavirus disease 2019 (COVID-19) pandemic outbreak, exacerbate its vulnerability. The Internet of things (IoT) is one of the disruptive technologies being adopted in food supply chain management (FSCM). This study aims to address the challenges of IoT adoption in the FSC by systematically analyzing the prior pertinent literature.Design/methodology/approachA structured literature review was used to collate a lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 120 publications
(236 reference statements)
0
43
0
1
Order By: Relevance
“…Benitez 28 advised collaboration with research & development centers in supply chain risk management to guide technological transformation by affording high-risk ventures. Aamer 37 identified data security and trust as significant concerns among the supply chain partners and data owners. To overcome this challenge, the authors suggested building a solid defense by deploying emerging technologies across the supply chain reinforcing cyber security, access control, data authentication, and customer privacy protection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Benitez 28 advised collaboration with research & development centers in supply chain risk management to guide technological transformation by affording high-risk ventures. Aamer 37 identified data security and trust as significant concerns among the supply chain partners and data owners. To overcome this challenge, the authors suggested building a solid defense by deploying emerging technologies across the supply chain reinforcing cyber security, access control, data authentication, and customer privacy protection.…”
Section: Discussionmentioning
confidence: 99%
“…Frederico, 1 Acioli, 6 Shao, 14 Andiyappillai, 30 Brandtner, 17 Hopkins, 43 Ramirez-Peña, Abad Fraga, 44 Ramirez-Peña, Mayuet, 45 Wang, 46 Dolgui, Ivanov, Sethi, 47 Krykavskyy, 48 Queiroz, Machado, 49 Gu, 19 Li, 50 Quayson 51 Internet of Things Mubarik, 13 Benitez, 28 Amer, 37 P.K. Dutta, 52 Galanakis, 18 Raji, 27 Yadav, 15 Chanchaichujit, 53 Haji, 20 Hossain, 54 Končar, 55 Kumar, 56 Ardito, 7 Chauhan, 25 Fernández-Caramés, 23 Mostafa 31 Big data Mubarik, 13 Gupta, 36 Benitez, 28 Amer, 37 Brandtner, 17 Lv, 54 Raji, 27 Hossain, 54 Ivanov, 41 Ardito, 7 Chauhan, 25 Fernández-Caramés, 23 Mostafa, 31 Queiroz & Pereira 57 Cloud computing Raji, 27 Chanchaichujit, 53 Haji, 20 Hossain, 54 Ivanov,…”
Section: General Industry 40 Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There also exists a gap in hardware related technical skills especially in industries such as food and pharmaceuticals where the devices cannot be easily embedded while ensuring quality and safety. Designing and controlling the IoT infrastructure remains a challenge [51]. Changes in the broader labor landscape will require an intervention from the policy makers to secure future skills and help SMEs cope with the change.…”
Section: Privacy and Surveillancementioning
confidence: 99%